Artificial Intelligence's Meaning Production between Branding Rhetoric and New Hybrids - Paolo Peverini (Ocula)
Advances in generative artificial intelligence in content production are fueling a heated debate on the outcomes of delegating these processes to text-to-text and text-to-image type systems, particularly with reference to the notions of creativity, authenticity, verisimilitude. Starting from these premise, and in continuity with the sociosemiotic perspective (Landowski 1989), the paper aims at analyzing a corpus of recent advertising campaigns co-produced with AI, or simulating co-production, investigating the ways in which this socio-technical phenomenon is reflected in the texts and discourses it produces. Relevant brand narratives play a decisive role in giving visibility to significant and controversial issues, up to the cultural tensions (Holt 2004) that invest the everyday life experience of subjects on a cognitive, pathemic and pragmatic level. Following this perspective, the paper therefore intends to explore the strategies adopted by some relevant brands to thematize the limits and potential of artificial intelligence tools. Specifically, it deals with the controversy over the naturalization processes of these devices, hence their ability to produce meaning effects capable of either supporting or hindering the acceptance of artificial intelligence and its wide and rapid diffusion in everyday life practices. By analyzing an exemplary textual corpus, this paper also aims to contribute to the theoretical advancement on the intersection of semiotic research on social phenomena and the work of Bruno Latour, focusing on the notions of enunciation, hybrid, and anthropomorphism.